Caracterização do comportamento de desgaste de cerâmicas de alumina densa : efeitos de parâmetros do ensaio do tipo pino no disco - Tedesco, Nadetsa Reginato (Universidade Federal de São Carlos, 2010)
Searching for wear resistant materials, attention has been paid to Si3N4, SiC, Al2O3 and ZrO2 ceramics due to their better properties as compared to other materials. Although ceramic are brittleness, improvements on the processing and by the addition of second phases to the ceramic matrix have lessen this restriction because of microstructure refinement. Therefore, some mechanical proprieties have been optimized e probably the wear resistance also. Among the ceramic composites, greater attention has been given to the alumina nanocomposites due to the improvements on the toughness, hardness and mechanical resistance. Wear research has been made in the literature but, a direct comparison between the many published works regarding this wear improvement is impossible due to the fact that wear resistance is a response of the microstructure, material and testing condition. So the work herein presented aim was to do a systematic study in the alumina wear based on the critical parameters which have to be controlled on a pin-on-disc test concerning about the mild and severe wear regime. Since, it was possible to describe a procedure to evaluate the alumina wear behavior and resistance in terms of applied load, sliding speed and environment. By the use of the study methodology proposed, it was possible to construct a simplify wear transition diagram which allowed to define parameters combination were alumina can be use as a wear resistance material
Characterization of the wear behavior of dense alumina ceramics: effects of the pin-on-disc test parameters
Keywords: Cerâmica; Alumina; Resistência ao desgaste; Pino no disco; Diagrama de desgaste; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA